COMPETÊNCIAS GERENCIAIS COMO APORTE À GESTÃO ESTRATÉGICA DE PESSOAS: ESTUDO DE CASO EM UMA INSTITUIÇÃO FEDERAL DE ENSINO SUPERIOR (IFES). - Dutra, Ana Lucia da Silva (2012)
This research aimed to investigate the possible impacts of the use of managerial skills in strategic people management in a Federal Institution of Higher Education, which is the Universidade Federal Fluminense, according to the vision of its managers. Based on Watson (2005), who believes that competent managers are competent learners, this research developed a case study, using qualitative methods. We used the Method Underlying Explanation of Discourse (MEDS), developed by Nicolaci-da-Costa (2004), with semistructured interviews. This method aimed to understand the views of senior managers who hold an executive position or gratified functions on the theme. According to the results, managers understand the importance of the management process to achieve the expected institutional results; they think that the use of managerial competencies is important to give support to this process; they recognize in themselves gaps of competency and they know there are discrepancies between what they believe to be necessary to the managerial process and what they observe in reality managerial at UFF. And, finally, there are barriers when trying to change this reality.